Gustatory disturbances occur in patients with head and neck cancer who undergo radiotherapy not directed to the oral cavity. (August 2019) - Barbosa da Silva, José Lucas; Doty, Richard L.; Miyazaki, João Victor Massamitsu Katayama; Borges, Ricardo; Pinna, Fábio de Rezende; Voegels, Richard Louis; Fornazieri, Marco Aurélio
Highlights: Radiotherapy impairs gustation even when the field of treatment does not include the oral cavity. Taste recovery occurs between 3 and 6 months after the radiotherapy and is independent of xerostomia. The identification of sweet and bitter tastes is most affected. Fourteen percent of the patients experienced qualitative taste distortions after radiotherapy. Abstract: Introduction: Even the most modern radiation techniques still result in some degree of toxicity to adjacent normal tissues. Consequently, the radiotherapy treatment in head and neck neoplasms potentially leads to gustatory dysfunction even in cases when the treatment area is outside or adjacent to the oral cavity. In this study we quantitatively and qualitatively assessed gustatory function in patients with head and neck cancers who underwent radiotherapy inside and outside of the oral cavity. Methods: Fifty-six patients with head and neck cancer responded to a specific questionnaire and had their gustatory function tested before, immediately after, and at 3 and 6 months following radiotherapy treatment. The irradiation field did not include the oral cavity in 29 patients and included it in 27 patients. Results: All patients suffered a severe loss of taste immediately after radiotherapy. The identification of sweet and bitter tastes decreased in both groups, but the sour decrement was exclusive to those who had the oral cavity irradiated. Fourteen percent of patients complained of qualitative changes of taste, namely taste distortions. No impact of xerostomia on the taste measures was apparent. Conclusion: We found that patients with head and neck neoplasms submitted to radiotherapy have disturbed taste even when irradiation does not include the oral cavity. This deficit is worse immediately after the end of radiotherapy. Our findings do not support the hypothesis that decreased salivary flow is the major cause for radiation-induced changes in taste function.